Longitudinal analysis of cardiovascular disease risk profile in neighbourhood poverty subgroups: 5-year results from an afterschool fitness programme in the USA. Issue 3 (24th November 2017) - D'Agostino, Emily M; Patel, Hersila H; Hansen, Eric; Mathew, M Sunil; Nardi, Maria; Messiah, Sarah E
Abstract : Background: The WHO calls for affordable population-based prevention strategies for reducing the global burden of cardiovascular disease (CVD) on morbidity and mortality; however, effective, sustainable and accessible community-based approaches for CVD prevention in at-risk youth have yet to be identified. We examined the effects of implementing a daily park-based afterschool fitness programme on youth CVD risk profiles over 5 years and across area poverty subgroups. Methods: The study included 2264 youth (mean age 9.4 years, 54% male, 50% Hispanic, 47% non-Hispanic black, 70% high/very high area poverty) in Miami, Florida, USA. We used three-level repeated measures mixed models to determine the longitudinal effects of programme participation on modifiable CVD outcomes (2010–2016). Results: Duration of programme participation was significantly associated with CVD risk profile improvements, including body mass index (BMI) z-score, diastolic/systolic blood pressure, skinfold thicknesses, waist–hip ratio, sit-ups, push-ups, Progressive Aerobic Cardiovascular Endurance Run (PACER) score, 400 m run time, probability of developing systolic/diastolic hypertension and overweight/obesity in high/very high poverty neighbourhoods (P<0.001). Diastolic blood pressure decreased 3.4 percentile points (95% CI −5.85 to −0.85), 8.1 percentile points (95% CI –11.98 to −4.26), 6.1 percentile points (95% CI −11.49 to −0.66), 7.6 percentile points (95% CI −15.33 to –0.15) and 11.4 percentile points (95% CI −25.32 to 2.61) for 1–5 years, respectively, in high/very high poverty areas. In contrast, significant improvements were found only for PACER score and waist–hip ratio in low/mid poverty areas. Conclusion: This analysis presents compelling evidence demonstrating that park-based afterschool programmes can successfully maintain or improve at-risk youth CVD profiles over multiple years.